Building Bridges, Not Walls: Navigating Inter-Religious Conflict Over Worship Spaces in Aceh Singkil, Indonesia - Zain, Arifin; Maturidi, Maturidi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to identify the factors causing conflict, analyse conflict resolution methods, and determine the factors that hinder the resolution of conflicts related to the construction of houses of worship in Aceh Singkil District. The research employs a qualitative approach, collecting data through observation, interviews, and documentation studies. The findings reveal that inter-religious conflicts, particularly between Muslims and Christians, are triggered by the construction of houses of worship that do not comply with agreed-upon terms. The Aceh Singkil government has taken several steps to address these conflicts, such as socialising regulations, promoting mutual respect among religious adherents, conducting Focus Group Discussions (FGDs), and holding dialogues with conflicting parties. However, the resolution is hindered by factors like the binding nature of the 1979 Agreement, incomplete conflict resolution efforts, political issues, suboptimal performance of relevant institutions, and the fact that the clergy are not indigenous. This research provides valuable insights into the dynamics of inter-religious conflicts in Aceh Singkil, highlighting the complex interplay of social, political, and legal factors in conflict resolution.